Hodnocení stavu pozemních komunikací v ČR - Nowak, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Bakalářská práce mapuje technický stav silniční sítě v ČR. Pozornost je zvláště věnována silnicím II. a III. třídy a problematice financování sítě pozemních komunikací.

This Bachelor’s Thesis maps technical condition of road network in Czech Republic. Attention is especially devoted to 2ND and 3RD class road and the issue of financing the infrastructure.
Road condition rating in Czech Republic
Keywords: Spolehlivost vozovky; provozní způsobilost; únosnost vozovky; trvanlivost obrusné vrstvy; poruchy vozovek; systém hospodaření s vozovkou; Reliability of the pavements; operational eligibility; bearing capacity of pavement; surface course durability; failure of pavements; pavement management system